Protecting the Quality of Public Water-Supply Sources : A Guide for Water Utilities, Municipal Authorities, and Environmental Agencies - Foster, Stephen; Hirata, Richardo; Gomes, Daniel; D'Elia, Monica; Paris, Marta (World Bank, Washington, DC, 2012)
Water-supply quality is too often taken for granted. Because we can see rivers and streams, they command most attention when talk turns to water quality but subsurface aquifers are every bit as important as a source of public water-supply and are also under threat of pollution. Acting now to protect them makes sound economic sense, because it is always cheaper to maintain the quality of groundwater resources, and of individual water-supply sources, than to mitigate the damage once done. But timely action depends on awareness of the urgent need to protect groundwater and to do this the authors must be able to identify clearly the threats they face. Because it is unrealistic to prohibit all potentially-polluting activities and the economically sound approach is to identify what are the most significant pollution threats, which parts of the land surface are most vulnerable to pollution of underlying groundwater and whether any such pollution will impact existing public water-supply sources. Such a procedure, which is described in this book, provides the direct focus required on the protection measures necessary to conserve the quality of any given groundwater supply source.